Soluble Form of Receptor for Advanced Glycation End Products Is Associated with Obesity and Metabolic Syndrome in Adolescents. (20th January 2014) - He, Chih-Tsueng; Lee, Chien-Hsing; Hsieh, Chang-Hsun; Hsiao, Fone-Ching; Kuo, Philip; Chu, Nain-Feng; Hung, Yi-Jen
Abstract : The aim of this cross-sectional study was to investigate the relationship between soluble form of receptor for advanced glycation end products (sRAGE), obesity, and metabolic syndrome (MetS) in adolescents. A total of 522 male and 561 female adolescents were enrolled into the final analyses. Anthropometric parameters, blood pressure, blood biochemistry, fasting insulin, and plasma sRAGE levels were measured. In males, sRAGE was significantly and inversely correlated with waist circumference (WC), body mass index (BMI), systolic blood pressure, triglyceride (TG), low density lipoprotein cholesterol (LDL-C), and homeostasis model assessment-insulin resistance (HOMA-IR). Only WC and BMI were significantly and inversely correlated with sRAGE in females. Using linear regression analysis adjusting for age and gender, significant association was found between sRAGE and WC, BMI, TG, LDL-C, and HOMA-IR in adolescents of either gender (P < 0.05 ). This association was abolished when further adjusting BMI. In addition, sRAGE was significantly and inversely correlated with the increasing number of components of MetS in males (P for trend = 0.006) but not in females (P for trend = 0.422). In conclusion, plasma sRAGE is associated with obesity and MetS among adolescents. BMI may be the most important determinant of sRAGE levels in adolescents.